An overview of e-consumer protection in sale of goods contracts in Malaysia - Amin, Naemah; Mohd Noor, Roshaslizawati (2012)
Legal protection towards e-consumers should be given equal emphasis as perceived by consumers who opt for face-to-face transactions. Unfortunately, nowadays, e-consumer protection remains regulated by traditional rules not specifically devoted to the online world. The explosive growth in cyberspace has led to some new problems and challenges pertaining to the legal protection of consumers. The perennial problem that needs considerable attention is the inadequacy of the existing legislation in Malaysia to meet the basic needs of online consumers. Even though the Consumer Protection Act 1999 (CPA) was amended in 2007 in order to protect the interests of e-consumers, the question remains as to how far the CPA and other existing legislation, namely the Contracts Act 1950, Sale of Goods Act 1957, Direct Sales and Anti-Pyramid Scheme Act 1993 and Electronics Commerce Act 2006 can protect e-consumers in sale of goods contracts. Therefore, this paper is tasked to generally analyze the extent to which present related e-commerce legislations in Malaysia can provide protection for e-consumers and to evaluate the efficacy of the current legislative framework in preserving the interests of e-consumers in order to overcome their anxieties as well as building up their confidence in purchasing goods online.